Criteria guiding mathematics professors practice in engineering basic science courses - Garcés-Córdova, Walmer (2022)
The study aims to infer the criteria that guide the practice of professors to explain mathematics, specifically derivatives, in a basic science course in the engineering program. This qualitative research of a multiple case study seeks to understand the teaching of differential calculus through the analysis of the practices of a group of seven professors, and the reflection on these practices when they implement their classes in engineering faculties of public and private universities in Lima, Peru. Each professor’s class was recorded. The criteria they follow to design and implement the classes were inferred, taking the didactic suitability criteria as a reference, which were also used to design the semi-structured interview questionnaire. Triangulation was done between what professors say and what they have been observed to do. It was noted that mathematics professors in engineering programs are completely conditioned by the subject syllabus when developing their derivative classes, as well as by the means and teaching resources and the availability of time for their differential calculus classes. Therefore, it is concluded that the priority criterion of the group of participating professors is meeting the curriculum in the time scheduled. On the other hand, they give more importance to adequately managing group interaction than teaching quality mathematics to be learned in a significant manner by students.